Video Communication With Cognitively Intact Nursing Home Residents: A Scoping Review. (August 2019) - Schuster, Amy M.; Hunter, Elizabeth G.
Limited research exists examining video communication among cognitively intact nursing home residents to connect with family. This scoping review evaluated existing literature for video communication usage with nursing home residents, family, and nursing homes. A comprehensive search was completed using PubMed and EBSCOhost (including AgeLine, CINAHL, and PsycINFO) between 1972 and 2016 to locate English-language articles. The analysis identified five eligible studies (four involved an intervention, one assessed family views) meeting inclusion criteria. Findings included, seeing family members separated by distance, seeing other parts of their life, and visually monitoring resident's health. Participants described frustration with technology limitations, such as video or audio lag. Current literature does not show a comprehensive assessment of video communication usage for residents, family, and nursing homes. Future studies should address the complexity of the intersection of the person, nursing home, and families in terms of potential benefits and capability of video communication use with residents.